Splendid isolation : Asim Abu Shakra, Irma Blank, Forrest Bess, Hélène Amouzou, Frank Walter, Hervé Yamguen, Danny Bergeman, Salam Atta Sabri, Louise Bourgeois, Zehra Doğan, Dom Sylvester Houédard, Eugenio Dittborn, Adrien Vescovi, Majd Abdel Hamid, Sheroanawe Hakihiiwe, David Byrd, Hessie, Nalini Malani, Derek Jarman, Shuvinai Ashoona, Judith Scott, Luciano Perna. - Fol, Carine; D'Ambrosio, Myrna; Haloköngäs, Amanda; Boon, Tanja; Hoste, Ann; Van Cauteren, Philippe; Vandenbroeck, Liesje (Gent : S.M.A.K., 2022)
Shakra, Asim Abu ; Blank, Irma ; Bess, Forrest ; Amouzou, Hélène ; Walter, Frank ; Yamguen, Hervé ; Bergeman, Danny ; Sabri, Salam Atta ; Bourgeois, Louise ; Doğan, Zehra ; Houédard, Dom Sylverster ; Dittborn, Eugenio ; Vescovi, Adrien ; Hamid, Majd Abdel ; Hakihiiwe, Sheroanawe ; Byrd, David ; Hessie ; Malani, Nalini ; Jarman, Derek ; Ashoona, Shuvinai ; Scott, Judith ; Perna, Luciano.
Spendid Isolation is a group exhibition that aims to explore the special conditions of living in solitude, and more specifically, the creative impulses that this way of life coan nurture. The exhibition brings together artists from different generations and different countries, and focuses on the artistic output that arises from living under self-imposed or forced restrictions.
Splendid isolation, S.M.A.K., Gent, 14 May 2022-18 Sept 2022
boek
Keywords: Blank, Irma; Bourgeois, Louise; Doğan, Zehra; Hamid, Majd Abdel; Al Atassi, Mohamed Ali; Jarman, Derek; Malani, Nalini; Walter, Frank; Yamguen, Hervé